421 Platform Speaker: Assessment of Pasture Supplementation Needs with Modern Computer Models. (7th December 2018) - Tedeschi, L; Cannas, A; Fonseca, M; Molle, G
Abstract: The majority of ruminants in the world are grazers. Thus, the proper supplementation of energy and nutrients to grazing ruminants is essential to ensure their level of production meets their genetic potential (i.e., precision feeding), leading to sustainable livestock production scenarios. However, an adequate provision of supplements depends on the accurate determination of the nutritive value of the forage, which is a function of how much nutrients can be extracted from the forage by the ruminant animal and an accurate assessment of energy and nutrient requirements by the grazing animal. Nutritive indices have been developed to provide nutritional information on forage quality and animal intake, but they are simplifications of a much more complicated system. Nutrition models have tackled these aspects from a more comprehensive viewpoint, but there still room for holistic concepts to fuse critical elements (soil, climate, forage, and animal) together in developing more mechanistic tools. For instance, the determination of forage consumption by grazing ruminants is substandard at least, though it has been evolving at a somewhat slower pace than anticipated. Additional areas that need improvements in the supply side are accounting for substitution rates of concentrate feeds (protein and energy) and forage fiber level, how grazing on grasses-legume mixtures impact forage consumption and long-term pasture maintenance, assessment of quantity and quality of forages, and animal selectivity. On the requirement side, needed improvements include an adequate assessment of energy expenditure for physical activity, the impact of global warming condition on energy and nutrient requirements and grazing activities, and nutrient requirements for efficient animals. Therefore, integrated agricultural models must represent ruminants as an additional trophic level, so the synchronization and flow of nutrients are used to predict forage availability, and animal feed requirement for drought-prone regions and different management strategies with and without ruminants can be evaluated.